Canva Effectiveness in Teaching Writing Procedure Text - Yuda, Andika Fadilah Pratama; Putri, Sherly Citra; Jannah, Irham Miftakhul; Prastyo, Hari (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2025)
This study aimed to investigate the effectiveness of using Canva application as a learning media to enhance ninth-grade students’ writing skills in procedure texts at junior high school. It adopted quasi-experimental approach using quantitative research design. The main research instrument was written test including pre-test and post-test. Data were analyzed by using t-test and the results showed significant increase from average post-test score (95.00) compared to the average pre-test score (74.00). The finding supported t-test analysis, whereas Sig. (2-tailed) value of 0.000, below 0.05 significance level. From the result above, it was concluded that the use of Canva application was very effective to improve students' writing skills in procedure texts. Canva application was proved as innovative and interactive tool that facilitated teaching and learning process. It helped students overcome their writing difficulties.